OPTIMIZING THE PROGRESS OF EDUCATIONAL INSTITUTIONS THROUGH TEACHER TRAINING IN IMPROVING THE FIELD OF SUSTAINABLE EDUCATION - Syafi’i, Moh.; Ahmad Thoyib Mas’udi; Jamilah, Ida Lutfiyatul; Mustadi, Mustadi (Community Development Journal : Jurnal Pengabdian Masyarakat, 2024)
This community service project was initiated in response to a critical need for improved teaching practices and sustainable educational development. This service aims to empower teachers with the skills and knowledge necessary to integrate sustainability into their teaching methods, thereby improving the overall quality of education and student engagement. The method involves a direct and comprehensive teacher training program through a Participatory Action Research (PAR) approach, which includes workshops, seminars, and ongoing support systems such as peer mentoring and online forums. This training focuses on interactive and student-centered teaching strategies, as well as the incorporation of sustainability concepts into the curriculum. Additionally, the project engages community stakeholders through workshops and information sessions to ensure alignment with local needs and to encourage community support. The results of this service are significant, with marked improvements in teaching practices, teacher confidence, and student outcomes. Teachers report increasing adoption of interactive methods and sustainability concepts, thereby increasing student engagement and academic performance. The project also successfully created a culture of continuous professional growth among teachers, supported by regular follow-up and community engagement. In conclusion, this project shows that comprehensive and ongoing professional development, coupled with strong community engagement, can produce sustainable advances in educational practice.